CORRELATION OF EDUCATIONAL MARKETING BASED ON CUSTOMER RELATIONSHIP MANAGEMENT AND QUALITY OF MARKETING SERVICES WITH SCHOOL DECISION MAKING AT SDIT NUURUSSHIDIIQ - Awaliatul Laely, Umi; Gloria, Ria Yulia; Suklani, Suklani (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2026)
Educational marketing is undergoing a transformation with the implementation of Customer Relationship Management which plays a strategic role in building personal and sustainable relationships with parents, students and the community. Customer Relationship Management Integration not only increases school loyalty and reputation, but also significantly improves the quality of educational services, including the learning process, administrative services, and student character development. Customer Relationship Management and the quality of educational services are important factors influencing parents' decision-making in choosing a school, as both create satisfaction, trust, and loyalty towards the educational institution, which ultimately determines the choice of school for their children. This study used a quantitative method with a correlational research type. Data collection techniques were carried out through a questionnaire with answer choices using a Likert scale given to parents or guardians of students. Data analysis techniques in this study used multiple linear regression tests, t-tests, and f-tests to test the hypotheses. The results of the study indicate that: 1) marketing of education based on Customer Relationship Management has a significant positive correlation with decision making, as evidenced by a significance value of 0,000<0.05, 2) the quality of educational services has a significant positive correlation with decision making, as evidenced by a significance value of 0,000<0.05, 3) marketing of education based on Customer Relationship Management and the quality of educational services has a significant positive correlation with decision making, as evidenced by a significance value of 0,000<0.05.